Activité physique The Benefits of active transport related to health and well-being among some Algerian postmen - Zerf, Mohammed (Santé, 2017)
Introduction. Nowadays, the world is facing an unusual increase in obesity rates, interpreted by similar studies to the reduction of physical activity time, compared to the inactivity time relative to our daily life. The case of workers/postmen, who need to walk or cycle up for six miles each weekday as aerobic exercise to achieve weight loss relative to enhance physical fitness, was studied. Objectives. To examine the influence of this phenomenon, this study was based on the transportation used by our factors. Population and Methods: Factors (n= 54) from Algeria Telecom of Naama was participated in this study. Their daily tasks were evaluated, according to the delivery packages in which they deliver with different means of transportation. While to test the transportation effectiveness and its relationship to worker health, we rely on the Rockport Fitness Walking Test to assess aerobic fitness, which is a well-known approach to weight loss and fitness. Results. Based on applied statistics, we confirmed the need to encourage our workers to use active transportation on foot or by bike. Active transportation was an effective way to improve the physical fitness and well-being of the body weight of our workers. Conclusion. Active transportation as walking or bicycling is qualified to meet the physiological capacity required in a daily physical condition to improve or maintain fitness relative to the motorcycle as an inactive means of transportation.
Keywords: Transportation; Health; Well-being; Algerian postal worker